Analysis of Financial Performance in Determining Going Concern Audit Opinions - Nur Jannah Abdi Aziz; Pradani, Tiara; Putri, Pretisila Kartika (Jurnal Akuntansi, 2024)
The stability of a company’s financial health is a critical factor in determining its ability to continue operations. This study examines the role of financial performance in influencing auditors' decisions when issuing going concern audit opinions. The research employs a quantitative approach with a sample of 51 companies in the plantation sub-sector listed on the Indonesia Stock Exchange (IDX) between 2020 and 2023. Using logistic regression, this study evaluates the impact of solvency and profitability ratios on auditors’ judgments. The findings indicate that these financial performance indicators, when analyzed independently, do not significantly influence going concern opinions. However, when assessed collectively, financial performance plays a significant role in shaping auditors' assessments. The implications of this study highlight the necessity for auditors to consider broader financial distress indicators, prior going concern opinions, and other firm characteristics when evaluating business continuity. Keywords: audit opinion, financial performance